Thorndike’s Connectionism in Practice: A Qualitative Study of Arabic Morning Programs in Indonesia - Munazzalurrohmi, Muhammad; Mubarok, Khusnul; Rosyada, Amrina; Muzadi, Narul Hasyim; Warahmah, Mawadda (Asalibuna, 2025)
This research is important to raise as a reflection on the importance of applying discipline in the learning process, especially Arabic. Arabic. Thorndike's theory of behaviorism which discusses how to strengthen the relationship between stimulus and response is closely related to reflection in Arabic. Relationship between stimulus and response is closely related to the above reflection above. As a behaviorist approach emphasizing stimulus-response reinforcement, Connectionism provides a relevant theoretical lens for evaluating Arabic language learning practices. This study aims to analyze the Arabic Morning program based on the perspective of Thorndike's Connectionism theory which includes 3 aspects 1) aspects of the law of exercise 2) aspects of the law of cause and effect, and 3) aspects of the law of readiness. This research is a case study type with a descriptive approach. Data were collected by interview, observation, and documentation. The data came from 1) interviews with Arabic Morning tutors, 2) participant observation, and 3) Arabic Morning document review. The data analysis technique uses the Miles and Hubermann model which consists of three steps, namely data reduction, data presentation, and conclusion drawing. The results of the study show that three aspects of Thorndike's Connectionism theory have been applied. The forms of implementation are 1) the legal aspect of practice in the form of memorizing mufrodat, writing, and expressing Arabic sentences, 2) the legal aspect of cause and effect in the form of applying rewards and punishments, and 3) the aspect of readiness in the form of emphasis on students to have internal and external readiness in participating in the Arabic Morning program. Based on the results of the data analysis process, it is found that the three legal aspects of Thorndike's Connectionism theory have been fully implemented in Arabic language learning.